2022
DOI: 10.1155/2022/1281521
|View full text |Cite
|
Sign up to set email alerts
|

Gender Discrimination of Flower Buds of Mature Populus tomentosa by HPLC Fingerprint Combined with Chemometrics

Abstract: A high performance liquid chromatography-diode array detector (HPLC-DAD) was used to establish the HPLC fingerprint. Chemometrics methods were used to discriminate against the gender of flower buds of Populus tomentosa based on areas of common peaks calibrated with the HPLC fingerprint. The score plot of principal component analysis (PCA) showed a clear grouping trend (R2X, 0.753; Q2, 0.564) between female and male samples. Two groups were also well discriminated with orthogonal partial least squares-discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The mass spectrometry data of all batches of ALRP and HSP were imported into Markerview software for normalization of the detected peak ion intensity, and the processed data was imported into SIMCA for analysis. The R 2 X, R 2 Y, and Q 2 of this OPLS‐DA model were 0.826, 1, and 0.876, indicating the good fitting and predictive ability of the model 54 . As shown in Figure 7A, the ALRP and HSP were well distinguished, located on both sides of the X‐axis, respectively.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The mass spectrometry data of all batches of ALRP and HSP were imported into Markerview software for normalization of the detected peak ion intensity, and the processed data was imported into SIMCA for analysis. The R 2 X, R 2 Y, and Q 2 of this OPLS‐DA model were 0.826, 1, and 0.876, indicating the good fitting and predictive ability of the model 54 . As shown in Figure 7A, the ALRP and HSP were well distinguished, located on both sides of the X‐axis, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…The R 2 X, R 2 Y, and Q 2 of this OPLS-DA model were 0.826, 1, and 0.876, indicating the good fitting and predictive ability of the model. 54 As shown in Figure 7A, the ALRP and HSP were well distinguished, located on both sides of the X-axis, respectively. S-plot was displayed for selecting differential variables, as shown in Figure 7B.…”
Section: Analysis Of Differences Between Alrp and Hspmentioning
confidence: 83%
“…The result showed that the R 2 and Q 2 values on the left were less than the values they had originally on the right. The intercept of the regression line of Q 2 on the longitudinal axis was less than zero, thus suggesting that the OPLS‐DA model was not overfitting and was reliable (Z. Li, Wu, et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The intercept of the regression line of 𝑄 2 on the longitudinal axis was less than zero, thus suggesting that the OPLS-DA model was not overfitting and was reliable (Z. Li, Wu, et al, 2022).…”
Section: Opls-da Analysismentioning
confidence: 99%
See 1 more Smart Citation